Effect of resin impregnation on the transverse pressure dependence of the critical current in ReBCO Roebel cables. (3rd April 2019) - Gao, P; Wessel, W A J; Dhallé, M; Otten, S; Kario, A; Van Nugteren, J; Kirby, G; Bottura, L; ten Kate, H H J
Abstract: Re BCO Roebel cables are being developed as one of the promising routes towards much higher-field magnets for future particle accelerators. The Lorentz forces generated in such magnets lead to sizeable transverse pressure on the superconducting cables, in the present 15–20 T magnet designs of the order of 100–150 MPa. Contrary to single Re BCO coated conductors, unprotected Roebel cable due to their uneven surface, start to degrade already with 40 MPa as shown in earlier work. Previous publications also showed that proper impregnation with epoxy resin can dramatically improve the transverse pressure tolerance of a relatively simple model cable with 10 Re BCO strands, assembled from SuperPower tape. However, the epoxy resins used until now are not suitable for large-scale magnet vacuum impregnation. For this reason, an alternative impregnation method using CTD-101K with S2 glass fibers has been implemented. The present paper expands further on the effect of impregnation on the transverse pressure susceptibility of Roebel cables. Three cables, with an architecture that is directly relevant for the so-called EuCARD-2 accelerator demonstrator magnet, were investigated with a variable transverse mechanical load at 4.2 K in a 10.5 T perpendicular magnetic field. The new cables feature a relatively long transposition length of 226 mm and comprise 15 strands of either SuperPower or Bruker coated conductor. For reference, one of the new SuperPower tape based cables was impregnated with the same resin as the one used in the earlier publications. The other cables were impregnated using the new method. The critical current at 4.2 K of the Bruker tape Roebel cable is 2.5 to 3 times higher than that of the SuperPower tape ones with similar architecture. Remarkably no critical current degradation was observed for transverse pressure up to 440 MPa in the SuperPower tape cables and up to 370 MPa in the Bruker tape cable. These values by far satisfy the design requirements of presently envisaged 20 T class accelerator demonstrator magnets.